A Nanosized CoNi Hydroxide@Hydroxysulfide Core–Shell Heterostructure for Enhanced Oxygen Evolution. Issue 4 (5th December 2018) - Wang, Bin; Tang, Cheng; Wang, Hao‐Fan; Chen, Xiao; Cao, Rui; Zhang, Qiang
Abstract: A cost‐effective and highly efficient oxygen evolution reaction (OER) electrocatalyst will be significant for the future energy scenario. The emergence of the core–shell heterostructure has invoked new feasibilities to inspire the full potential of non‐precious‐metal candidates. The shells always have a large thickness, affording robust mechanical properties under harsh reaction conditions, which limits the full exposure of active sites with highly intrinsic reactivity and extrinsic physicochemical characters for optimal performance. Herein, a nanosized CoNi hydroxide@hydroxysulfide core–shell heterostructure is fabricated via an ethanol‐modified surface sulfurization method. Such a synthetic strategy is demonstrated to be effective in controllably fabricating a core–shell heterostructure with an ultrathin shell (4 nm) and favorable exposure of active sites, resulting in a moderately regulated electronic structure, remarkably facilitated charge transfer, fully exposed active sites, and a strongly coupled heterointerface for energy electrocatalysis. Consequently, the as‐obtained hydroxide@hydroxysulfide core–shell is revealed as a superior OER catalyst, with a small overpotential of 274.0 mV required for 10.0 mA cm −2, a low Tafel slope of 45.0 mV dec −1, and a favorable long‐term stability in 0.10 M KOH. This work affords fresh concepts and strategies for the design and fabrication of advanced core–shell heterostructures, and thus opens up new avenues for the targeted development of high‐performance energy materials. Abstract : A CoNi hydroxide@hydroxysulfide core–shell heterostructure is fabricated via an ethanol‐modified surface sulfurization method with favorable electronic and interface engineering, resulting in excellent intrinsic activity, favorable extrinsic physicochemical characters, and thereby superior water oxidation performances.